Fate and propagation of endogenously formed Tau aggregates in neuronal cells. Issue 12 (12th November 2020) - Chastagner, Patricia; Loria, Frida; Vargas, Jessica Y; Tois, Josh; I Diamond, Marc; Okafo, George; Brou, Christel; Zurzolo, Chiara
Abstract: Tau accumulation in the form of neurofibrillary tangles in the brain is a hallmark of tauopathies such as Alzheimer's disease (AD). Tau aggregates accumulate in brain regions in a defined spatiotemporal pattern and may induce the aggregation of native Tau in a prion‐like manner. However, the underlying mechanisms of cell‐to‐cell spreading of Tau pathology are unknown and could involve encapsulation within exosomes, trans‐synaptic passage, and tunneling nanotubes (TNTs). We have established a neuronal cell model to monitor both internalization of externally added fibrils, synthetic (K18) or Tau from AD brain extracts, and real‐time conversion of microtubule‐binding domain of Tau fused to a fluorescent marker into aggregates. We found that these endogenously formed deposits colabel with ubiquitin and p62 but are not recruited to macroautophagosomes, eventually escaping clearance. Furthermore, endogenous K18‐seeded Tau aggregates spread to neighboring cells where they seed new deposits. Transfer of Tau aggregates depends on direct cell contact, and they are found inside TNTs connecting neuronal cells. We further demonstrate that contact‐dependent transfer occurs in primary neurons and between neurons and astrocytes in organotypic cultures. SYNOPSIS: Using a neuronal cell reporter system, this study shows that exogenous and endogenous Tau fibrils seed Tau misfolding. Endogenously formed Tau aggregates block their own degradation through the autophagic pathway and are transferred through tunneling nanotubes (TNTs) to neighboring cells. A neuronal biosensor allows measuring the rates and kinetics of seeding of endogenous Tau aggregates in living cells. Synthetic and Alzheimer's disease (AD) patient‐derived fibrils seed endogenous aggregates following the same kinetics in the biosensor cell line. Endogenously formed aggregates escape autophagy and proteasome degradation. Tau aggregates are propagated mainly in a cell‐contact‐dependent manner, and are found inside TNTs. All these events may play key roles in the pathobiology of AD and other tauopathies. Abstract : Using a neuronal cell reporter system, this study shows that exogenous and endogenous Tau fibrils seed Tau misfolding. Endogenously formed Tau aggregates block their own degradation through the autophagic pathway and are transferred through tunneling nanotubes (TNTs) to neighboring cells.